Factors of the Effective Development of the St. Petersburg Instrument Engineering Cluster - Rodionov, Dmitriy Grigorievich; Kudryavtseva, Tatiana Jurievna (International Journal of Economics and Financial Issues, 2016)
The study analyzed the effectiveness of the cluster policy in the field of instrument engineering. Based on the study of theoretical and practical provisions, the identification of the main problems of the development of cluster projects was made; the concept of knowledge transfer was discussed and its relevance for the implementation of the cluster policy in the field of instrument engineering was determined; the methodology for assessing the effectiveness of the cluster policy was analyzed; the factors of the effectiveness of the development of the instrument engineering cluster were evaluated on the basis of the multiple correlation analysis. The study resulted in a direct correlation between the dynamics of the development of the instrument engineering cluster of St. Petersburg and the wages of employees of the enterprises in the cluster. Keywords: industrial cluster, instrument engineering, cluster policy, effectiveness, development, St. Petersburg. JEL Classifications: O25, O31.